Japan out of the Lost Decade : Divine Wind or Firms' Effort? - Tokutsu, Ichiro (IMF Working Papers; Working Paper ;, 2012)
A surge of exports in the 2000s helped Japan exit the severe decade-long stagnation known as the lost decade. Using panel data of Japanese exporting firms, we examine the sources of the export surge during this period. One view argues that the so-called "divine wind" or exogenous external demand boosted Japanese exports. The other view emphasizes the role of supply factors such as productivity gains, materialized after long-fought restructuring efforts during the lost decade. Estimating the firm-level export function allows us to assess the relative importance of these demand and supply factors. Evidence shows that firms' efforts were more important than the divine wind.